Bioinformatics approach to enhance the undergraduate biology students’ understanding of plant terpenoid - Risanti Dhaniaputri; Hadi Suwono; Betty Lukiati (University of Muhammadiyah Malang, 2024)
Plant metabolite compounds have been applied on plant cellular metabolism, produces organic and inorganic compounds, primary and secondary bioactive molecules, such as glucose, amino acids, fat acids, alkaloids, flavonoids, and terpenoids. Undergraduate biology students learn about the plant terpenoid assisted by bioinformatics to store, manage, and interpret the molecular information about these compounds. This research aims to observe the students’ understanding of terpenoid through implementing bioinformatics approach. Besides, to investigate how practice the bioinformatics technology in learning terpenoid may impact students' comprehension of plant metabolism domain and their acquisition of bioinformatics inquiry skills. Bioinformatics is a computational database that relies on digital repositories of molecular biology informations. Data analysis was in the form of quantitative and qualitative descriptive using module learning resources based on terpenoid research and assisted by bioinformatics. The results indicate that students’ comprehension of learning and understanding terpenoid has improved, identification and analysis processes of article reviews showed that students were able to discuss and interpret research finding in silico bioinformatics using molecular docking procedures. Assessment of bioinformatics skills showed that all undergraduate biology students could follow the direct instructions well, answer the questions, practice the dry-lab experimental, and formulate the conclusion correctly.